Identification of stable reference genes for qRT-PCR in Stropharia rugosoannulata using mRNA-sequencing data - Xiaohua Zhang; Xuesong Li; Rong Hua; Yuan Fang; Tingsong Yue; Jianying Li; Yuxun Lu; Wansong Yue; Zhanghui Gao; Shaoxiong Liu; Dafeng Sun (PLoS ONE, 2025)
Quantitative real-time PCR (qRT-PCR) is a well-established and reliable technology utilized for the rapid and accurate quantification of gene expression changes. The selection of stable reference genes is necessary to analyse qRT-PCR data and ensure gene expression studies reliability. Stropharia rugosoannulata, commonly known as the wine-cap Stropharia mushroom, ranks among the top ten internationally traded mushrooms. In the present study, six novel candidate reference genes were selected from S. rugosoannulata transcriptome, alongside four traditional reference genes that displayed stable expression levels in S. rugosoannulata. Three widely used software (geNorm, NormFinder, and BestKeeper) were employed to analyse ten candidate reference genes, and the final ranking of reference genes was determined through RefFinder. The results indicated that UBP exhibited the highest stability across various developmental stages of red and yellow S. rugosoannulata, while RPB2 and GAPDH showed the least stability. These novel reference genes demonstrated significantly superior stability to other four traditional genes across nearly all developmental stages. In conclusion, Our findings provide robust guidelines for selecting suitable reference genes, thereby enhancing the reliability of qRT-PCR normalization in Stropharia rugosoannulata.